Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Wolaita Sodo University - International Livestock Research Institute; Wolaita Sodo University (2021)
Memorandum of understanding (MOU) between the International Livestock Research Institute (ILRI) and Wolaita Sodo University. MOU signed on December 23, 2021, by Jimmy Smith, Director-General of ILRI and Takele Tadesse, President of Wolaita Sodo University.